Effects of spent mushroom substrate-derived biochar on soil CO2 and N2O emissions depend on pyrolysis temperature. (May 2020) - Deng, Bangliang; Shi, Yanzhen; Zhang, Ling; Fang, Haifu; Gao, Yu; Luo, Laicong; Feng, Weixun; Hu, Xiaofei; Wan, Songze; Huang, Wei; Guo, Xiaomin; Siemann, Evan
Abstract: Edible mushroom cultivation is an important industry in intensively managed forest understories. However, proper disposal of spent mushroom substrate (SMS) presents a challenge to its sustainable development. Biochar derived from SMS could be used to improve soil quality while providing a solution for SMS disposal. But SMS biochar pyrolyzed at different temperatures may alter carbon dioxide (CO2 ) and nitrous oxide (N2 O) emissions associated with global warming, especially under the context of nitrogen (N) addition and warming. We conducted a factorial incubation study to examine greenhouse gas emissions and N transformations in moso bamboo forest soil amended with SMS-biochar (control vs. pyrolyzed at 300, 450 or 600 °C) in different N-addition (0 or 100 mg N kg -1 soil) and temperature (20, 25 or 30 °C) treatments. Pyrolysis temperature affected pH, C and N of SMS-biochars. N-transformations depended on the interaction of pyrolysis temperature, N-addition, and incubation temperature but were generally lower with 450 °C biochar addition. Soil N2 O emissions increased with N-addition and they were more sensitive to incubation temperatures without biochar. Soil CO2 emissions increased with incubation temperature or biochar pyrolyzed at lower temperatures. Pyrolysis temperature might have regulated the effects of SMS-derived biochar on N2 O emissions via changes in dissolved C, N, pH and associated changes in soil microbial community compositions. Because of the importance of sustainable development of this understory industry, amending soils with biochar produced at higher temperatures may be the best strategy for both the disposal of SMS and the mitigation of greenhouse gas emissions. Graphical abstract: Image 1 Highlights: PH of spent mushroom substrate (SMS) biochar increased with pyrolysis temperature. SMS-biochar reduced the temperature sensitivity of soil N2 O emission rates. Lower pyrolysis temperature SMS-biochar increased CO2 emissions. Spent mushroom substrate biochar pyrolyzed at 450 °C decreased nitrification rate.